Educação e projetos de desenvolvimento no Brasil : a expansão da rede federal de educação profissional e tecnológica no início do século XXI - Mattos, Marilucia dos Santos (2013)
This work aims to analyze existing relations between the expansion of the federal network of professional and technological education and development project in socioeconomic and educational in the current Brazil. Presents a brief recovery on theories of development and its relation to policies for professional education in Brazil, having as object the federal network of professional and technological education. By means of the document analysis, performs a characterization of the current process of expansion of the federal network of professional and technological education, making comparisons with other historical periods and analyzing its contradictions, possibilities and limitations. Concludes that the trajectory of professional education in Brazil has always maintained relationship with development projects having as periods of evidence national developmentalism and the process of network expansion experienced this new century. This relationship, although characteristics and distinct periods is strongly marked by the influence of the ideology of "human capital theory", which puts into question the significant expansion of the Brazilian professional education and development project recorded in the current period that despite represent an advance in relation to the neoliberal project implemented in 1990 does not represent a project to break with it